Random Skin Biopsy Is a Useful Procedure in the Evaluation of Hemophagocytic Lymphohistiocytosis: A Case Report and Review of Literature. (27th December 2022) - Hegazy, Shaymaa; Moesch, John; Guerrero, Angela; Ho, Jonhan; Karunamurthy, Arivarasan
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a rare, life-threatening syndrome, characterized by aberrant activation of T lymphocytes and macrophages leading to hypercytokinemia. HLH can be familial or a result of various secondary etiologies. We present a case of a 46-year-old woman with a past medical history of multiple sclerosis on rituximab who presented as a transfer from an outside hospital with numerous clinical abnormalities including recurrent episodes of fever of unknown origin for 3 weeks, persistent leukocytosis, hypertriglyceridemia, and steatohepatitis. Given the uncertain nature of her illness, she underwent a random skin biopsy from the abdominal region to exclude hematolymphoid malignancy. Histopathology revealed a brisk histiocytic rich dermal infiltrate accompanied by perivascular lymphocytic infiltrate. The histiocytes were enlarged and positive for muraminadase and CD68 stains exhibiting hemophagocytosis focally. As per the HLH-2004 protocol, our patient met the diagnostic criteria of HLH. Concurrent bone marrow biopsy revealed similar rare hemophagocytosis. Cytogenetics and molecular studies were negative, supporting secondary HLH.